Investigation of deformation zone parameter at multichannel angular extrusion (Modern Problems of Metallurgy, 2022)
The paper presents the results of research on the modern process of multichannel angular extrusion. Analysis of the literature has shown that the use of non-equal angular extrusion leads to a smaller size of microstructure in one pass than equal-angular compression. Accordingly, non-uniform angular extrusion is well suited for the formation and changing of fine-grained metal structure, and also significantly increases its strength, ductility and toughness due to shear deformation. However, the known methods of non-uniform angular pressing are mostly used for the manufacture of intermediate products (rods, strip), which to achieve the required level of properties require additional processing. Additional thermal or deformation processing could have a negative impact on the structure and properties of the product. Thus, the urgent task is to develop and study processes in which intense plastic deformation is the final operation. One of these processes is multichannel angular extrusion. The aim of the study is to determine the characteristics of the deformation zone and plastic flow of the metal in this process. The analysis of the grid has allowed to identify certain elements of the deformation zone. A special tool has been developed to provide multi-channel angular extrusion. The peculiarity of the developed tool is the matrix integrated into the container and made collapsible. This design provides removal of the extruded profile after processing. It has been found that the central layers of metal deform more easily, and the layers, the flow of which slows down due to contact friction between the tool and the workpiece, deform with a delay. The adequacy of the mathematical model of the process developed in the QForm © program was also confirmed with the help of experimental data.